(untitled) (Asian Journal of Social Science Studies, 2020)
Different country showed different governing capacity to the COVID-19 pandemic in 2020. With reference to the classical concept of embedded autonomy, as used in developmental state of political theory, this paper aims to study the capacity and progression of democratic country, Taiwan, in its fight with the emergence of the COVID-19 pandemic and how democratic state, civil society and bureaucrats have affected the response and measures. Taiwan‟s case provides a valuable empirical contribution to the understanding of the long term effect of embedded autonomy in a democratic country. This study argues that democracy does matter to fight Covid-19 pandemic, moreover, the legacy of embedded autonomy can be expanded beyond economic development, and successfully used to explain Taiwan‟s capacity to fight the COVID-19 pandemic in its early stage. Key observations and discussion addressed in this study includes, first, the extent to which the concept of embedded autonomy is applicable in evaluating and in shaping Taiwan‟s efforts to manage the pandemic; second, the extent to which the political system is better at managing COVID-19 crisis by comparing democratic Taiwan and authoritarian China. A central finding of this paper is that, democracy has proven it has the edge in coping with COVID-19 pandemic practically. Theoretically, Taiwan‟s case demonstrates a valuable and supplementary example to Evans and Heller (2018) on their broadening view of embedded autonomy. The legacy of the developmental state is applicable to explain Taiwan‟s immediate and effective response to the COVID-19 outbreak. A reachable governance to fight COVID-19 lies in „the nature of democracy‟ and „the legacy of embedded autonomy‟.